On some interesting trends in research of steel and composite structures = O pewnych interesujących trendach w badaniach konstrukcji stalowych i kompozytowych - Marcinowski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is a kind of introduction to the special issue of CEER devoted to metal and composite structures. Papers collected in this issue were ordered from Authors who took part in International Conference on Metal Structures which was held in Zielona Góra in 2016. Selection of Authors and theme of ordered papers were done in cooperation with Metal Structures Section of the Civil Engineering Committee of the Polish Academy of Sciences. Selected papers included in this special issue of CEER were shortly presented in this editorial.
Keywords: steel structures; composite structures; research trends; ordered papers; konstrukcje stalowe; konstrukcje kompozytowe; kierunki badań; referaty zamówione